AN ANALYSIS OF POLITENESS STRATEGIES ON THE INDAH G SHOW "ARE WE THE GENERATION OF LOW STANDARDS?”: A PRAGMATIC STUDY - Hamid, Hastuti. A.; Elysa Hartati, (Journal of Innovation Research and Knowledge, 2024)
Communication is a social process in which a person conveys the intent and purpose to the interlocutor and gets reciprocity from the interlocutor. In communication there are various rules to achieve the purpose of the interaction, it is politeness. Nowadays, politeness can be found in various talk shows or television programs. The Indah G Show is an Indonesian talk show that covers various topics, including controversial societal issues, social issues, gender, women, and political matters. The program, which is hosted by Indah Gunawan, also known as Indah G, is distinguished by her open approach to discussing topics. This study aims to describe the type of politeness strategy employed by the host and reveal how one’s characteristics presents politeness strategies in the way of communication. In this study, the researcher focuses on analyzing the politeness strategies using Brown and Levinson's theory of politeness. This study is a qualitative study, the data collection technique was done by listening and note-taking technique. The collected data was transcribed and coded according to the politeness strategies identified in Brown and Levinson's theory of Politeness Strategy.